A Review of Information and Communication Technology Enhanced Social Work Interventions. (January 2016) - Chan, Chitat; Holosko, Michael J.
Objectives: Information and communications technology (ICT) has impacted almost all human service disciplines and currently is evolving in social work. This study provides a systematic review of ICT-enhanced social work interventions, with particular reference to their intervention fidelity (IF), validity, and the role of ICT in the helping relationship process. Method: We assessed specific articles published in journals classified under the "Social Work" research area in the Social Science Citation Index (SSCI; N = 17). Results: All studies that met specific criteria indicated positive intervention outcomes, most of them were of "good" or "fair" quality in terms of their validity, and almost all of them upheld IF. However, there was room for improvement in the conceptualization component of the ICT intervention application. Conclusions: These ICT-enhanced intervention studies established a foundation to enable unique practice insights to advance social work practice knowledge. Additional practice and research in this area are necessary in order to further our understanding about ICT and their use in social work interventions. Implications are discussed and suggestions are provided.